225Ac‐labeled CD33‐targeting antibody reverses resistance to Bcl‐2 inhibitor venetoclax in acute myeloid leukemia models - Ravendra Garg (Cancer Medicine, 2021)
ABSTRACT Purpose Despite the availability of new drugs, many patients with acute myeloid leukemia (AML) do not achieve remission and outcomes remain poor. Venetoclax is a promising new therapy approved for use in combination with a hypomethylating agent or with low‐dose cytarabine for the treatment of newly diagnosed older AML patients or those ineligible for intensive chemotherapy. 225Actinium‐lintuzumab (225Ac‐lintuzumab) is a clinical stage radioimmunotherapy targeting CD33 that has shown evidence of single‐agent activity in relapsed/refractory AML. Increased expression of MCL‐1 is a mediator of resistance to venetoclax in cancer. Experimental design Here we investigated the potential for 225Ac‐lintuzumab‐directed DNA damage to suppress MCL‐1 levels as a possible mechanism of reversing resistance to venetoclax in two preclinical in vivo models of AML. Results We demonstrated that 225Ac‐lintuzumab in combination with venetoclax induced a synergistic increase in tumor cell killing compared to treatment with either drug alone in venetoclax‐resistant AML cell lines through both an induction of double‐stranded DNA breaks (DSBs) and depletion of MCL‐1 protein levels. Further, this combination led to significant tumor growth control and prolonged survival benefit in venetoclax‐resistant in vivo AML models. Conclusions There results suggest that the combination of 225Ac‐lintuzumab with venetoclax is a promising therapeutic strategy for the treatment of patients with venetoclax‐resistant AML. Clinical trial of this combination therapy (NCT03867682) is currently ongoing.